Educação das relações étnico-raciais: contribuições de cursos de formação continuada para professoras(es) - Luiz, Maria Fernanda (2013)
This research investigates the contributions for changes (or not) in the pedagogical practices of teachers of the early years of basic education stemming educational processes triggered in training courses relating to ethnic-racial theme. From the implementation of the law 10.639/032, topics related to the history and culture african- Brazilian and African became compulsory in the curriculum of public and private networks, which creates demand for conducting continuing education courses for teachers of different levels of education in these operating systems. Thus, were invited to participate in this study, black and non-black teachers in the early years of basic education who have participated in continuing education courses related to ethnic-racial theme. The research data were collected through in-depth conversations held with these teachers. The relevance of this study to the field of education is confirmed by the possibility of reflection on points that continuing education courses contributed or not to change the practice of these teachers, issues that need to be rethought in formulating future courses as well as the influence of subjective questions pertaining relating to the experiences of teachers and influence the understanding and coherency of the theme.